Estudo teórico comparativo do complexo [RUCl3(H2O)2gly] - Sousa, Kátia Meirelles Duarte de (2016)
The complex [RuCl3(H2O)2(Gly)] synthesized (CHAGAS, 2015) showed leishmanicidal activity and interaction with tumor cells, but there is a need for determining their isomeric structure responsible for these characteristics. Thus, the aim of this study is to determine the possible geometric isomer of (CHAGAS, 2015) molecule through computational methods and comparison with experimental data. The theoretical calculation of the isomers provided data that allow the distinction of its structures theoretically, promoting data for future work. The results of the study suggest isomers fac-cis as possible structure obtained experimentally.